Development of magnesium biocomposites with hydroxyapatite or carbonate apatite reinforcement as implant candidates: A review - Yusuf Subagyo; Baharudin Priwintoko; Rifky Ismail; Deni Fajar Fitriyana; I Nyoman Jujur; Iwan Setyadi; Galih Taqwatomo (Mechanical Engineering for Society and Industry, 2023)
Metal materials used as bone implants are not new today. In fact, almost 70% of implant materials are made of metal. Magnesium biocomposites with Carbonate Apatite or Hydroxyapatite reinforcements have promising potential as implants, one of the properties of these composites is biocompatible and bioactive to accelerate bone growth. There have been many studies on the development of Mg-CAp and Mg-HAp as biocomposite implant materials. Various methods of making these biocomposites have been carried out, such as sintering, microwave, coating, casting, and extrusion. From the fabrication process, observations were made regarding mechanical properties and chemical structure. The results show that CAp and HAp can suppress the corrosion rate of Magnesium, which is one of the weak properties that must be improved. Then it can increase the biological activity of Mg composites and has the ability of bone induction and bone conduction. In addition, the mechanical properties have increased in tensile, compression, and microhardness testing. However, so far, the research on Mg-HAp and Mg-CAp has only been limited to animal testing and has not been applied to humans. So, the potential for development and research is still open actually to be implemented in the orthopedic field.